Peningkatan Motorik Kasar Anak Usia Dini Melalui Kegiatan Tari Kreasi Di Taman Kanak-kanak - Yusri, Auliya Rizkyani; Fitri, Riskal; Nirwana, Nirwana (Ihya Ulum: Early Childhood Education Journal, 2024)
This study aims to improve children's gross motor skills using dance movement activities. The type of research conducted to improve children's gross motor skills is classroom action research (CAR) in the form of collaboration between teachers and two cycles with creative dance activities. Where in one cycle there is planning, observation and reflection. The results showed that creation dance can improve gross motor skills in group B children at Ihya Al Ulum Kindergarten Makassar. Gross motor skills of children that can be improved include. coordination of locomotor movements. This can be seen from the initial action observation that children's gross motor skills have not developed 75.00% in group B children, in cycle I still need a lot of action because there has not been much change in the undeveloped criteria owned by 62.50% in group B children and in cycle II it developed very well 81.25% in group B children.